2006
DOI: 10.1063/1.2218336
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate state polarization in multiphoton ionization of HCl

Abstract: The paper presents the detailed theoretical description of the intermediate state polarization and photofragment angular distribution in resonance enhanced multiphoton ionization (REMPI) of molecules and the experimental investigation of these effects in the E(1)Sigma(+) and V(1)Sigma(+) states of HCl populated by two-photon transitions. It is shown that the intermediate state polarization can be characterized by the universal parameter b which is in general a complex number containing information about the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 49 publications
6
60
0
1
Order By: Relevance
“…A compact and convenient spherical tensor expression for the intensity of the REMPI 2 + 1 signal which is valid for the pure linearly, or circularly polarized probe light can be written in the form 102,103 …”
Section: Appendix: Detection Of the Reaction Product Angular Momentummentioning
confidence: 99%
“…A compact and convenient spherical tensor expression for the intensity of the REMPI 2 + 1 signal which is valid for the pure linearly, or circularly polarized probe light can be written in the form 102,103 …”
Section: Appendix: Detection Of the Reaction Product Angular Momentummentioning
confidence: 99%
“…), see [7,8,[11][12][13][14][15][16] and references therein, however a number of studies have been carried out in the gas phase [17][18][19][20][21][22][23][24][25]. The gas phase/molecular beam studies are of fundamental importance for understanding the TPEF dynamics of polyatomic molecules in the collision-free regime because they can be supported by high accuracy quantum mechanical ab initio calculations which in most cases are not available for the condensed matter studies.…”
Section: Introductionmentioning
confidence: 99%
“…The angular momentum polarization produced by twophoton absorption can be described by formalisms outlined by Manzhos et al [1] and by Chichinin et al [21]. In the axial recoil approximation the angular photoproduct distribution can be presented as a product of the excited state axis spatial distribution and the angular distribution of the photofragments produced via photolysis from an unpolarized excited state.…”
Section: Angular Distributions Of Photoproductsmentioning
confidence: 99%
“…Following the formalism outlined by Chichinin et al [21] one obtains for the observed angular distribution of the photoproduct P(θ):…”
Section: Angular Distributions Of Photoproductsmentioning
confidence: 99%
See 1 more Smart Citation